تأثير اتجاهات خطوط بناء النموذج الأساسي للبنطلون الجينز البناتي على الأداء الحركي في المرحلة العمرية "9-12" - حسين، عبدالله عبدالمنعم عبدالله; أبو السعود، إيمان رأفت فريد (جامعة المنيا - كلية التربية النوعية, 2021)
أصبح البنطلون الجينز من الملابس الأساسية المناسبة عمليا للمرأة العاملة وطالبات الجامعة وكذلك الأطفال. وتساهم الملابس في تنمية الذوق الجمالي والإحساس بالبهجة والراحة عند الأطفال بصفة خاصة. وجدير بالذكر أن تنفيذ البنطلون الجينز خاصة البناتي منه يحتاج إلى مهارة في كلا من بناء النموذج وتصميم الموديل عليه. ومن الملاحظ في الأسواق توافر البنطلون الجينز للمرحلة العمرية من 9-12 سنة (محل الدراسة) بشكل مختلف ومتنوع في قياساته وغير معتمد على الجداول القياسية للأجسام المصرية، لذا هدفت هذه الدراسة إلى محاوله إيجاد طريقه مثلى قدر المستطاع لبناء النموذج الأساسي للبنطلون الجينز للأطفال تتوافر فيه أسس الضبط الجيد والراحة على الجسم، فكان لابد من وضع جدول قياسي للقياسات الأساسية اللازمة لبناء نموذج البنطلون الجينز البناتي بالمرحلة المحددة، بهدف بناء نموذج مقترح بدراسة تأثير زوايا ميل (6°- 01°) درجتان لميل خط حجر الأمام والخلف وتأثير خطوط النموذج على الأداء الحركي، وعليه قدم الباحثان مجموعة من النماذج المقترحة بالقياسات تخص المرحلة المحددة من خلال عينة عمدية بسيطة تكونت من (411) بنت بمحافظة المنوفية، وتم التوصل إلى وضع جدول مقترح لقياسات البنطلون البناتي، وتم اختيار مفردات العينة من أجسام البنات التي تمثل متوسط القياس للفترة المحددة من (8-01) وإعداد نموذجان لكل بنت بزاويتين ميل للحجر الأمامي والخلفي بواقع (7) نماذج، وتم عرضهم على الأساتذة المحكمين وعددهم (01) محكم في مجال الملابس والنسيج بكليات الاقتصاد المنزلي وكليات التربية النوعية، والمتخصصين بالصناعة، وكذا تم أخذ آراء عينة من المستهلكين (24) من البنات وأولياء الأمور وتمت معالجة النتائج إحصائيا وتوصل البحث إلى أن أفضل زاوية ميل مناسبة لبناء النموذج الأساسي للبنطلون البناتي هي زاوية (6°).
Jeans pant have become partically appropriate basic clothing for working women, University students and children. Clothes contribute to the development of aethetic tast, comfort and joy feelings, especially for children It should be noted that the implementation of jeans especially for girls, requires skill in both building the pattern and designing the model on it. Additionally, it is noticeable in the market that jeans pant are available for the age stage 9-12 (subject of study) in different and varied way in their measurement and not based on the standard tables of the Egyptian bodies. Therefore, this study aimed to find an optimal way as possible to build the basic pattern of jeans for children With physical comfort and well fit on the body Our study included: Setting a table for the basic measurement to build a pattern of girls' jeans at the specified stage with the aim of building a proposed pattern by studying the angles of Inclination (7-10) two degrees of inclination of the front and back rise line And its effect on kinetic performance, the researches presented a set of suggested pattern with the measurement of the Specific stage is concerned with a simple intentional sample consisting of 500 girls in Menoufia governorate Measurements' table was reached and the sample items were selected from the girls' bodies that represent the average measurement for the subject stage and two models were prepared for each girl with two agles of inclination For the front and back within eight models and were evaluated by 12 referees in clothing and textile field in Home Economics and Specific Education college as well as industry specialists and the opinion of 35 consumers from girls and their parents was Taken into account, the data were statistically analyzed Based on the obtained results, the best angle of inclination in basic pattern of jeans for girls was 7 degree Inclination (7-10) two degrees of inclination of the front and back stone line.
Keywords: الملابس الجاهزة -- الجينز البناتي -- الأداء الحركي -- علم الأرجونوميكس -- القيم الجمالية